Compound Heterozygosity of the Functionally Null Cdh23(v-ngt) and Hypomorphic Cdh23(ahl) Alleles Leads to Early-onset Progressive Hearing Loss in Mice - Miyasaka, Yuki (Japanese Association for Laboratory Animal Science, 2013)
The waltzer (v) mouse mutant harbors a mutation in Cadherin 23 (Cdh23) and is a model for Usher syndrome type 1D, which is characterized by congenital deafness, vestibular dysfunction, and prepubertal onset of progressive retinitis pigmentosa. In mice, functionally null Cdh23 mutations affect stereociliary morphogenesis and the polarity of both cochlear and vestibular hair cells. In contrast, the murine Cdh23(ahl) allele, which harbors a hypomorphic mutation, causes an increase in susceptibility to age-related hearing loss in many inbred strains. We produced congenic mice by crossing mice carrying the v niigata (Cdh23(v-ngt)) null allele with mice carrying the hypomorphic Cdh23(ahl) allele on the C57BL/6J background, and we then analyzed the animals’ balance and hearing phenotypes. Although the Cdh23(v-ngt/ahl) compound heterozygous mice exhibited normal vestibular function, their hearing ability was abnormal: the mice exhibited higher thresholds of auditory brainstem response (ABR) and rapid age-dependent elevation of ABR thresholds compared with Cdh23(ahl/ahl) homozygous mice. We found that the stereocilia developed normally but were progressively disrupted in Cdh23(v-ngt/ahl) mice. In hair cells, CDH23 localizes to the tip links of stereocilia, which are thought to gate the mechanoelectrical transduction channels in hair cells. We hypothesize that the reduction of Cdh23 gene dosage in Cdh23(v-ngt/ahl) mice leads to the degeneration of stereocilia, which consequently reduces tip link tension. These findings indicate that CDH23 plays an important role in the maintenance of tip links during the aging process.